Dark Side of Digital Economy: A Criminal Law Study of Economic Crimes on Digital Platforms - Harly Clifford Jonas Salmon (Journal of Strafvordering Indonesian, 2026)
The development of the digital economy through various information technology-based platforms has created a major transformation in people's economic activities. On the other hand, this development has also given rise to various new forms of economic crime that exploit digital systems as a means to obtain unlawful profits. This situation poses challenges for the criminal law system in anticipating and addressing platform-based economic crimes. This study aims to analyze the criminal law construction for economic crimes on digital platforms and examine the ambiguity of norms regarding criminal liability for platform-based economic crimes. The research method used is normative legal research with a statutory and conceptual approach. Legal materials are analyzed qualitatively to identify the alignment between digital economic developments and applicable legal regulations. The results show that criminal law regulations related to digital economic activities in Indonesia are still partial and do not specifically regulate various forms of economic crimes on digital platforms. The ambiguity of norms regarding the responsibilities of platform providers, the determination of legal subjects, and electronic evidence-based evidentiary mechanisms creates legal uncertainty and has the potential to hamper the effectiveness of law enforcement. Therefore, a reformulation of criminal law policies is needed that is more responsive, integrative, and adaptive to developments in digital technology in order to create legal certainty and optimal protection for the community in the digital economy ecosystem.